2013
DOI: 10.25071/1920-7336.37507
|View full text |Cite
|
Sign up to set email alerts
|

Resilience among Single Adult Female Refugees in Hamilton, Ontario

Abstract: Single adult females remain among the most vulnerable of all refugee populations. However, there is a lack of research on supporting and empowering these women. There is a new interest in identifying factors that reinforce resilience and, ultimately, adjustment to the host country. In line with the current work on resilience, semi-structured, indepth, personal interviews with single refugee women were conducted in the city of Hamilton, Ontario. A grounded theory approach revealed participants’ perspectives on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…The mothers in this study reported several factors that led to increased resilience, including receiving emotional, childcare and technological support from partners and children, spending time outdoors in socially distanced settings and trying to keep a positive or optimistic perspective. These findings align with the existing literature pertaining to experiences of resilience in the context of the COVID-19 pandemic [24] , [55] , as well as with pre-pandemic literature on resilience in refugee mothers during resettlement [52] , [56] , [57] . Additional coping mechanisms included adopting a global perspective and collectivist attitude (i.e., framing one's own challenges against the backdrop of the pandemic being a global event affecting everyone), which was a common practice to situate, contextualize and lessen one's perceived struggles.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The mothers in this study reported several factors that led to increased resilience, including receiving emotional, childcare and technological support from partners and children, spending time outdoors in socially distanced settings and trying to keep a positive or optimistic perspective. These findings align with the existing literature pertaining to experiences of resilience in the context of the COVID-19 pandemic [24] , [55] , as well as with pre-pandemic literature on resilience in refugee mothers during resettlement [52] , [56] , [57] . Additional coping mechanisms included adopting a global perspective and collectivist attitude (i.e., framing one's own challenges against the backdrop of the pandemic being a global event affecting everyone), which was a common practice to situate, contextualize and lessen one's perceived struggles.…”
Section: Discussionsupporting
confidence: 87%
“…Seminal works in resilience literature call for a shift in the conceptualization and analysis of resilience from the perspective of individual protective factors toward a conception of resilience as a collective process that includes community and structural forces [29] , [59] , [60] . Termed “collective resilience” [56] , this broadened conceptualization establishes resilience as a continuous process that incorporates the individual, family and wider social environments, and recognizes that resilience is not inherent to individuals or households but is built up through support systems [59] , such as those provided by government and non-governmental organizations. Indeed, our findings underscore that extra-household support systems are critical to refugee mothers' and families' wellbeing during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…For many WoRB, it was identified that connecting with a community from their country of origin provided them with an ongoing connection with their culture and language of origin. This is consistent with previous research by Sesay (2015) and Chung et al (2013), which identified that ongoing connection with a community from their culture of origin provided WoRB with an identify and self-worth while navigating a new environment and informal support systems. Despite this, the current study identified that this is particularly difficult in regional locations due to a lack of critical mass.…”
Section: Factors Contributing To Wellbeing and Coping During Resettlementsupporting
confidence: 92%
“…In addition, participants stated that having good friends made them feel cheerful and supported. Newbold (2013) reported that social and family support, along with individual characteristics, were very important to feelings of wellbeing [32].…”
Section: Discussionmentioning
confidence: 99%